THE CORRELATION BETWEEN PHYSIOLOGICAL AND BIOCHEMICAL INDEXES OF BOARS SEMEN - Ільченко, М. О. (Scientific Progress & Innovations, 2013)
It was studied the physiological and biochemistry status of semen in boars with different sperm quality. From physiological indexes were studied: the volume, the common number of sperm, the concentration, movement of semen, termoresistential test and termostres test. The biochemical indexes: general protein and its fractions, activity of AlAT, AsAT and LDG, creatinine, urea, cholesterol, triglycerides, phosphorus, calcium. It was determined the correlation only between the separate of them.